Effects of Stem Malalignment in Cementless Hip Arthroplasty: a Computational Study - Halim Abdullah, Abdul; M. Mohsien, Nik; Syahmi Yusof, Muhammad; Aznan, Nabila; Hisyam Marwan, Shahrul (International Journal of Engineering and Technology, 2018)
Implant loosening and deformation issues contribute to the instability of the hip arthroplasty. Prosthesis stem malalignment can occur in varus, anteversion and retroversion in different degrees due to several reasons. In this study, computational analysis of cementless hip arthroplasty with different stem malalignment cases was conducted to investigate the biomechanical effects in hip arthroplasty. Five hip arthroplasty models were developed using finite element analysis which are straight/aligned model, malalignment models at varus +3Â°, varus -3Â°, sagittal flexed +3Â°, and sagittal extended -3Â°. Results show that different pattern of stress distribution was observed in each malalignment case. The varus -3Â° malalignment model had demonstrated the greatest risk of failure based on the resulting stress distribution and total deformation.Â Â Â